2015
DOI: 10.3390/sports3030202
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kettlebell Swing Load and Cadence on Physiological, Perceptual and Mechanical Variables

Abstract: Abstract:This study compared the physiological, perceptual and mechanical responses to kettlebell swings at different loads and swing speeds. Following familiarization 16 strength trained participants (10 males, six females, mean age ± SD = 23 ± 2.9) performed four trials: 2 min kettlebell swings with an 8 kg kettlebell at a fast cadence; 2 min kettlebell swings with an 8 kg kettlebell at a slow cadence; 4 min kettlebell swings with a 4 kg kettlebell at a fast cadence; 4 min kettlebell swings with a 4 kg kettl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 10 publications
4
20
0
Order By: Relevance
“…Training style/technique was unclear or not reported in 21 studies (43%). Three studies were given 2 category allocations [57–59] and 3 were uncategorised, deemed incompatible for synthesis [6062].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Training style/technique was unclear or not reported in 21 studies (43%). Three studies were given 2 category allocations [57–59] and 3 were uncategorised, deemed incompatible for synthesis [6062].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers suggested that the resultant shoulder-dominant exercise likely inflated the physiological variables. In addition, swings have been reported to become perceptually harder with increasing bell weight [59], and reduced rest periods have significantly increased metabolic response when volume-matched with low load kettlebells [87]. The effect of different recovery strategies on lactate clearance following two-handed swings to volitional failure has been reported [90].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kettlebell sport originated in the 1700s [1] in Russia where the first recorded competition was held in 1948 [2]. Since about the year 2000, kettlebells have become a part of the mainstream fitness industry, functional fitness and CrossFit, and the sport is becoming increasingly popular [3].…”
Section: Introductionmentioning
confidence: 99%
“…This would benefit track and field athletes more so than athletes involved in other sports (e.g., soccer, basketball, rugby) since the PAP effects will only last a short period of time. Whilst the PAP effect is generally observed with relative loads ≥ 60% 1RM [ 17 ], the loads used with KBS are typically prescribed based on a specific absolute load and have not exceeded 32 kg [ 26 , 29 , 30 , 31 , 32 ]. One possible reason for not expressing KBS loads based on a % 1RM could be due to the manner KBS are performed i.e., rapidly, which is not suited for 1RM testing.…”
Section: Introductionmentioning
confidence: 99%